Why audiences’ voice on developing anti-smoking messages matters - Rizanna Rosemary; Azman, Zakirah; Ade Irma (Penerbit Universiti Kebangsaan Malaysia, 2022)
Mediated health campaigns are a significant promotive and preventive approach to public health. However, most health communication and campaigns in Indonesia tend to deliver explicit messages about the danger of addictive substances. For example, smoking is framed as harmful and unfavourable. Anti-smoking Public Service Advertising (PSA) depicts the severe adverse effect of smoking on health, sometimes resulting in people resisting the message. In contrast, pro-smoking through tobacco advertisements is associated with fun and enjoyable behaviour, encouraging people to smoke or start smoking. Besides quality, anti-smoking PSAs in the country cannot compete with accessible cigarette advertising in terms of quantity. As a result, intervention to prevent tobacco use remains lacking. The effectiveness of anti-smoking PSA is usually assessed by looking at and counting the significant impact of the messages on people’s intention to change their behaviour. This top-down approach is missing from understanding why people perceive the messages as meaningful and how they are likely to accept or reject them, particularly where smoking remains socially and culturally normalised, like in Indonesia. By reviewing the relevant literature on audience research, this paper aims to propose the cultural media audience as a valuable approach and framework in health communication and provide an analysis of some mediated smoking campaigns in Indonesia. The existing PSA tends to underscore people’s perceptions and expectations of the messages. It is argued that a cultural-media audience approach allows for staging people’s voices about persuasive health messages and helps to develop meaningful smoking-related interventions or campaigns.